Aerobic Exercise and Eucalyptus Globulus: Cardio-affective effects on recovery and stress - Alfredo Anderson Teixeira-Araujo; Jackson R.G.S. Almeida; Loumaíra Carvalho da Cruz; Xirley P Nunes; Sérgio Rodrigues Moreira (International Journal of Cardiovascular Practice, 2017)
Introduction: It is necessary to investigate the interrelation between physical exercise and aromatherapy, regarding cardiovascular and affective functions of human. Thus, the aim of this study was to evaluate the effects of aerobic exercise (AE) and eucalyptus essential oil (EO) in cardiovascular and affective responses.Methods: Twelve adults (19-39 years) performed in a randomized order in different days: 1. AE session; 2. Inhalation of EO session; 3. AE + EO session and; 4. Control session. In each session remained at rest over 15min plus 5min to inhaling EO or blank air in Control session. The AE was 15 min run/walk at 80-85% of maximum heart rate. After recovery (30 min) the Cold Pressor Test (CPT) was applied. At rest, recovery and during CPT were measured cardiovascular and affective variables.Results: The variation of systolic blood pressure in the CPT was attenuated by AE +EO (12.3 ± 14.9 mmHg) and EO (12.6 ± 6.7 mmHg) compared to Control (17.3 ± 6.5 mmHg; P < 0.05). AE + EO increased pleasure in recovery (1′ = 1.2 ± 1.9 pts and 30′= 0.6 ± 1.1 pts) and reduced displeasure in stress (-3.4 ± 1.7 pts) when compared to Control in recovery (1′= -0.5 ± 1.4 pts and 30′= -0.7 ± 1.5 pts, respectively; P < 0.05) and stress (-4.6 ± 1.8 pts; P < 0.05).Conclusions: We conclude that aerobic exercise and eucalyptus essential oil attenuated cardiovascular responses and modulated the affect on recovery and stress.